MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN COURSE REVIEW HORAY - Suriati Suriati (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This study aims to determine the learning model that is effective and efficient in teaching integer material. The subjects in this study were Class I Students of SD Negeri 010087 Selawan district Kisaran Timur academic year 2018/2019. Based on the results of the study, it was found that: (1) The results of the learning process through the Course Review Horay learning method reached an average value of 76.46 in the first cycle and in the second cycle the average score reached 83.29; (2) Percentage of classical learning completeness in the first cycle reached 64.29% after the first cycle and in the second cycle it reached 92.86%. It can be concluded that the learning model of the horay review course can improve mathematics learning outcomes of first grade students of SD Negeri 010087 Selawan district Kisaran Timur academic year 2018/2019. Keyword: course review horay Abstrak: Penelitian ini bertujuan untuk mengetahui model pembelajaran yang efektif dan efisien dalam mengajarkan materi bilangan bulat. Subjek dalam penelitian ini adalah Siswa Kelas I SDN 010087 Selawan kec. Kota Kisaran Timur TP. 2018/2019. Berdasarkan hasil penelitian diperoleh bahwa: (1) Hasil proses belajar melalui metode pembelajaran Course Review Horay mencapai nilai rata-rata 76,46 pada siklus I dan pada siklus II nilai rata-rata mencapai 83,29; (2) Presentase ketuntasan belajar klasikal pada siklus I mencapai 64,29% setelah siklus I dan pada siklus II mencapai 92,86%. Dapat disimpulkan bahwa model pembelajaran course review horay dapat meningkatkan hasil belajar matematika siswa kelas I SDN 010087 Selawan kec. Kota Kisaran Timur TP. 2018/2019. Kata kunci: course review horay